Efecto del falso Tabaco sobre la Mosca de la Fruta genero Anastrepha, en Laboratorio. - Pérez Yapud, David Sebastián (2020)
The present research was carried out in Latacunga County, in the salache sector in the Entomological Laboratory of the Technical University of Cotopaxi, with the objective of observing the effect of false tobacco on the fruit fly Anastrepha, in laboratory conditions. It was used the t Student test (statistical deductive test) with a control of 0cc/l, molasses-based food and a treatment with 5cc/l of False Tobacco Bioinsecticide. The methodology to follow was to use 50 flies of the fruit fly of the genus Anastrepha S, taking twenty five insects between males and females as control and equal amount of insects to proceed to apply the already elaborated bioinsecticide of false tobacco (Nicotiana Glauca), contained in a 500 ml container, in which it was proceeded to apply a dose of 5cc in each sponge of 2x2 cm all this carried out in twenty five plastic glasses of 15 cm as a den of the insects, the data collection was carried out every day after having applied the bioinsecticide and the food based on molasses, for which it took a time of 5 min to count the dead flies and to take out the glasses. The days in study to control the fly were 24 days for the control (0cc/l) and 6 days for the treatment (5cc/l). The research expressed the following results: that the treatment with a dose of 5cc/l of bioinsecticide of false tobacco obtained an average of 3 dead individuals per day being the one that obtained greater control and the highest average and of smaller control is the control at 0 cc/l with an average of 10.88 dead individuals per day. Thanks to this research, it was possible to demonstrate that the fake tobacco bio-insecticide is effective in the control of the fruit fly of the genus ansatrepha.